Communication structure and the performance of organisational teams - Kovačič, Helena (Teorija in praksa, 2011)
Relationship between communication structure of organisational teams and their performance is becoming increasingly important as more and more modern organisations move beyond their internal and external boundaries. Such a context provides room for the communication and co-operation of groups of individuals that cut across the various parts of the organisation. This article shows that the flattening of the hierarchy alone, which contributes to connectivity across the organisation, is not sufficient for successful cross-unit team collaboration. We support this discussion with the results of a study of two teams differing in their performances where a significant relationship was found between centralisation and team performance.
Keywords: Organizacije; Organizations; Team work; Timsko delo; Communication; Komuniciranje; Uspešnost; Successfulness; skupinsko delo; sodelovanje